Impact of Ownership Structure on the Performance & Profitability of Banks. - G, DR. SURESH.; F, MARY LAVANYA.; ANGEL, ITTAMALLA SONA (The journal of contemporary issues in business and government, 2021)
The Ownership structure of Banks play an important role in determining the profitability and performance of the banks. The Banks performance acts as a major issue for the policy decision makers since it is the substratum for the stability and smooth functioning of the banking system. Thus, we tend to we focus on bank ownership defined as the amount of direct equity held by a majority shareholder in the banks who are categorized into concentrated ownership, moderate ownership, & Dispersed Ownership structure. In this article we have made an attempt to systematically review each paper and analyze the impact of Banks Ownership structure on the performance and profitability of the Banks in emerging economies and also the common methodologies and models used by the research scholars in their work. Thus, presenting a systematic review paper. In line with the literature, we present the following analyses of the Scholars. Concentrated Ownership structure leads to increase in Bank’s value & Performance & is also highly profitable whereas banks with Dispersed ownership structure are said to have lower return on asset & high performance & banks with Moderate ownership structure would lead to increase in return on equity. Government Owned banks on the other hand are proved to have higher credit risk, & higher insolvency risk & also have efficient loan quality and finally Foreign Ownership is said to have higher efficiency and competitiveness.